Neuroblastoma—A Neural Crest Derived Embryonal Malignancy - Johnsen, John Inge; Dyberg, Cecilia; Wickström, Malin (Frontiers in Molecular Neuroscience, 2019)
Neuroblastoma is a neural crest derived malignancy of the peripheral nervous system and is the most common and deadliest tumor of infancy. It is characterized by clinical heterogeneity with a disease spectrum ranging from spontaneous regression without any medical intervention to treatment resistant tumors with metastatic spread and poor patient survival. The events that lead to the development of neuroblastoma from the neural crest have not been fully elucidated. Here we discuss factors and processes within the neural crest that when dysregulated have the potential to be initiators or drivers of neuroblastoma development. A more precise biological understanding of neuroblastoma causes and cell of origin is highly warranted. This will give valuable information for the development of medicines that specifically target molecules within neuroblastoma cells and also give hint about the mechanisms behind treatment resistance that is frequently seen in neuroblastoma.